Dietary uptake of copper in freshwater rainbow trout (Oncorhynchus mykiss): A study of mechanisms - Nadella, Sunita Rao (My University, 2005)
In aquatic environments Cu is both a vital nutrient and an important toxicant. Consequently fish require Cu as a micronutrient and can obtain this metal from either water or their diet. Inadequate intake of Cu is associated with reduced growth and development, while decreased growth rates, mortality and reduced swimming capacity have been reported in fish when Cu accumulates in excess of cellular needs. Characterization of Cu uptake is therefore critical in understanding the dynamics that govern toxicity and the risks associated with exposure to an aquatic contaminant. While mechanisms of waterborne uptake and toxicity are well understood, far less is known about gastrointestinal Cu uptake in fish. In vivo and in vitro techniques were therefore used in this study to investigate dietary Cu uptake in freshwater rainbow trout. The mid and posterior regions of the intestine emerged as important sites for Cu absorption in trout, while the role of the stomach and anterior intestine in Cu absorption requires further investigation. The intestinal uptake route was kinetically characterized as a low affinity absorption pathway as compared to the branchial route. Cu uptake appeared to occur via a hypoxia-resistant, carrier-mediated, saturable process which could be fueled by Cu(II)^2+ at concentrations typically found in the fluid phase of chyme in the trout intestine. Experimental manipulation of mucosal NaCl levels stimulated Cu uptake, Na2SO4 had an identical effect, implicating Na rather than the anion. These responses were unrelated to solvent drag, osmotic pressure or changes in TEP. The presence of excess luminal Ag and L-histidine stimulated Cu and Na uptake indicating that a portion of Cu transport was mediated by a Na-Cu co-transport system. Partial inhibition of Cu and Na uptake by phenamil and hypercapnia stimulated Na and Cu transport suggest Cu entry could also occur via the apical Na channel. The Na-dependent mechanism thus either involves more than one component or a unique Na-Cu co-transport mechanism with these combined characteristics mediates part of Cu uptake. Cu uptake was sensitive to pH and competed by Fe and Zn implicating DMT1 in the transport of Cu in the trout intestine. These factors had no effect on Na uptake, leading to the identification of a Na-independent mechanism for Cu uptake in the trout intestine. While the Na dependent nature of Cu uptake and Ag stimulated Cu transport argue against a role for Ctrl in this process, Cu transport characteristics identified in this study compare well with a recently identified Cu transporter in Ctr1 deficient mouse embryonic cells, indicating the existence of a similar transport mechanism in the trout intestine.
Dietary uptake of copper in rainbow trout: A study of mechanisms
Keywords: diet; copper; freshwater; rainbow trout; Oncorhynchus mykiss; mechanisms; bioaccumulation; toxicity; stomach; anterior intestine